Effect of florfenicol and oxytetracycline treatments on the intensive larval culture of the Chilean scallop Argopecten purpuratus (Lamarck, 1819). Issue 1 (27th June 2012) - Miranda, Claudio D; Rojas, Rodrigo; Abarca, Alejandro; Hurtado, Luz
Abstract The administration of antimicrobials to control bacterial pathologies in Chilean scallop hatcheries is a frequent practice, but their effects on these cultures remained unknown. This study was undertaken to obtain information on the effect of the administration of florfenicol and oxytetracycline on the growth, survival and bacterial content of scallop larvae under farming conditions. Florfenicol‐treated cultures exhibited high survival rates (44% after 17 days of culture), whereas cultures not treated or treated with oxytetracycline collapsed after 11 days of culture. Surprisingly, no significant differences in the heterotrophic (Tukey test; P = 0.226) and Vibrio (Tukey test; P = 0.666) concentrations between the oxytetracycline‐treated and untreated larval cultures were observed. Otherwise, florfenicol administered directly into rearing tanks produced significantly higher larval growth (Tukey test; P = 0.0001) and survival (Tukey test; P = 0.011) than bath treatment. When 2 and 4 mg L−1 of florfenicol were compared, no significant differences in growth (t‐test; P = 0.4596) and survival (Tukey test; P = 0.057) were observed, suggesting that a concentration of 2 mg L−1 is sufficient to ensure larval production. The present results demonstrate the efficacy of florfenicol‐based therapy to increase larval survival and growth at commercial scale and prompt the necessity to standardize its use in Chilean scallop hatcheries.